1991
DOI: 10.1080/15298669191364965
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Work Loan and Respirator Wear on Postural Stability, Heart Rate, and Perceived Exertion

Abstract: The effects on postural stability (sway) were investigated for different work loads under conditions of wearing a full facepiece respirator and not wearing any respiratory protection device. Fifteen subjects accomplished light (40 W), moderate (85 W), and heavy (125 W) work loads under the two conditions. Measurements of postural sway were made immediately after each load by using a multicomponent, strain gage-type force platform. Changes in each subject's movement pattern of the center of pressure were quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
23
0
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(28 citation statements)
references
References 0 publications
3
23
0
2
Order By: Relevance
“…Some researchers suggested that sway length may not be a good parameter to evaluate postural balance; instead, sway length may be a good indicator for the evaluation of psychological and physiological workload, and fatigue-related sensory and functional variability (Holbein-Jenny et al, 2007;Seliga et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers suggested that sway length may not be a good parameter to evaluate postural balance; instead, sway length may be a good indicator for the evaluation of psychological and physiological workload, and fatigue-related sensory and functional variability (Holbein-Jenny et al, 2007;Seliga et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…In consequence, exercise and dehydration may impair postural equilibrium by inducing changes in one or more of the links in the postural control chain. Seliga et al (1991) postulated that central fatigue (diminished central nervous system stimulation to muscle) an d localized muscular fatigue are associated with increases in sway am plitude. According to Lundin et al (1993), decreased stability may result from local fatigue in leg muscles around the ankle.…”
Section: Discussionmentioning
confidence: 99%
“…Seliga et al (1991) reported that low intensity cycling exercise had a short-term detrimental eOE ect on postural stability. It is therefore im portant to determ ine whether fatigue and / or body water loss resulting from physical or thermal stress have an in¯uence on postural stability.…”
Section: Introductionmentioning
confidence: 99%
“…Protective eyewear can reduce visual fields and clarity and facemasks or respirators may impair visual sensory input, requiring the wearer to use compensating strategies to maintain or regain postural stability (Punakallio, Lusa, & Luukkonen, 2003; Seliga et al, 1991; Wade, Weimer, & David, 2004). While TPC appears to be associated with impaired balance, it is difficult to reconcile the conclusions of these studies due to the varied tests of balance, experimental conditions, and the evolution of TPC and SCBA design.…”
mentioning
confidence: 99%